Localization of integrin receptors for fibronectin, collagen, and laminin in human skin. Variable expression in basal and squamous cell carcinomas. - Peltonen, J (1989)
VLA integrins in human skin were examined by indirect immunofluorescence utilizing antibodies recognizing the beta 1, alpha 2, alpha 3, or alpha 5 subunits. Staining of fetal, newborn, or adult skin with antibodies to beta 1, alpha 2, or alpha 3 subunits gave essentially similar staining patterns: intense staining was associated with the basal layer of the epidermis, hair follicles, and blood vessel walls. The alpha 5 subunit could be detected only in epidermis and the inner root sheath of hair follicles in fetal skin. In epidermis, the staining reaction for the beta 1 subunit was not only found in sites interfacing with the basement membrane zone, but also around the entire periphery of these cells. We speculate that these receptors might have previously unrecognized functions in cell-cell interactions or that these findings may suggest the presence of previously unrecognized ligands in the intercellular spaces of keratinocytes. Examination of nine nodular basal cell carcinomas revealed a prominent staining reaction with anti-beta 1 and anti-alpha 3 antibodies at the periphery of the tumor islands. In contrast, staining of five squamous cell carcinomas revealed either the absence of integrins or altered and variable expression. Thus, matrix components and their receptors may participate in modulation of growth, development, and organization of human skin.